(untitled) (Research, Society and Development, 2021)
The Logistics Investment Program (PIL) was published during the first government (2011-2014) of President Dilma Rousseff. The PIL aimed to promote logistical innovation for Brazil. However, a set of power relations of the State, which occurred between the years 2013 and 2016, influenced and changed what was originally planned, in this context, a new legal system for the Brazilian port sector was created. Thus, the purpose of this article is to describe the strategies, guidelines and objectives of “PIL: seaports” analyzing important aspects of Law nº 12.815/13 (the legal framework for the Brazilian seaport sector), as well as, we will verify the class contradictions involved in the process. To this end, we carried out bibliographical, documentary and cyberspace research.